Comparative analysis of the hormone production and gene expression profiles in ovine uterus tissue during oestrus cycle synchronized using medroxyprogesterone acetate plus ECG and prostaglandin analogue - de Sousa Lima, Joaquim; da Silva Costa, Márcio; Pereira, Júlio Rodrigues; de Campos Ferreira, Guilherme José Bolzani; Faustino, Luciana Rocha; Alves, Carlos Eduardo Fonseca [UNESP]; Oba, Eunice [UNESP]; Ferreira, Anna Clara Accioly; de Figueiredo, José Ricardo; da Silva, Cleidson Manoel Gomes (Universidade Estadual de Londrina, 2021)
The combination of medroxyprogesterone acetate (MPA) and gonadotropin chorionic (eCG) has been widely used to synchronize oestrus cycle in sheep, but their effects on the gene expression in uterine tissue are yet to be elucidated. To evaluate the effect of MPA + eCG or prostaglandin analogue (PA) treatments on the rate of oestrus cycle synchronization, as well as further hormone production and gene expression profiles in uterine tissue, 14 Santa Inês ewes were randomly selected. The MPA + eCG group (n=7) received intravaginal insertion of MPA-impregnated sponges for 14 days and was administered 350 IU eCG on the day of sponge withdrawal. The PA group (n=7) was administered two doses of 100 µg of PA separated by 12 days. The ewes were assessed for the rate of oestrus cycle synchronization and the serum concentrations of progesterone (P4) and estradiol (E2). Additionally, the expression of estrogen receptor (ERα), progesterone receptor (P4R), and immunolocalization of interferon receptor (IFNAR1) in the uterine tissue samples collected 15th day post-mating were examined. The rate of oestrus cycle synchronization was 100% (n=7/7) and 57.14% (n=4/7) in the MPA + eCG and PA groups, respectively. Moreover, the MPA + eCG group exhibited higher serum concentration of P4 than the PA group (p < 0.05). However, the E2 serum concentration did not differ between the two groups (p > 0.05). The relative expression of P4R and ERα mRNA analyzed using real-time PCR and immunodetection of IFNAR1 were similar between the two groups tested (p > 0.05). Conclusively, MPA + eCG treatment improved the rate of oestrus cycle synchronization and endogenous P4 production; however, it did not affect the expression of sex steroid receptors and IFNAR1 in uterine ovine tissue.
Análise comparativa da produção de hormônios e perfis de expressão gênica em tecido uterino ovino durante o ciclo estral sincronizado usando acetato de medroxiprogesterona mais ECG e análogo de prostaglandina
Keywords: Estrogen receptor-α; IFNAR1; Oestrus cycle; Progesterone receptor; Sheep